Development of a uniform insolvency law in SADC : lessons from OHADA - Leno, Ngaundje Doris (Journal of African Law, 2013)
This article argues that, with the global or cross-border nature of many corporate activities, there is an increasing need for a uniform insolvency law approach to the financial distress of a corporation in the Southern African Development Community. In doing so, the article highlights lessons the community may learn from the Insolvency Act of the Organisation for the Harmonization of Business Law in Africa. Emphasis is given to that organization’s success in developing a uniform insolvency act (ie one which is directly applicable in its contracting states). The article also proposes a number of recommendations.
Accepted: 2014-02-28T11:57:54Z
Keywords: Africa; Bankruptcy; Business law; Financial distress; Insolvency Act; Insolvency law

The development of a commercial law structure in the SADC with specific reference to OHADA - Leno, Ngaundje Doris (University of Pretoria, 2013)
In a region where there is diversity of laws, the author maintains that law reform is a catalyst for investment and development. This thesis aims at demonstrating that OHADA provides practical lessons for the development of a uniform commercial law structure in the SADC. This is following OHADA’s success in developing uniform commercial rules that are directly applicable in the contracting states. To achieve this, the thesis uses a “structured focused comparison” methodology that allows for two separate, but structurally linked accounts of the structures of both organisations. In exploring the structures of both organisations, the thesis endeavours to: determine whether there is the need for the development of a commercial law structure in the SADC; whether such a structure can be developed within the current SADC structure and whether OHADA can serve as a possible model for the SADC. The findings show that no part of the African continent has witnessed regional legal reform on the scale of that initiated by OHADA. It equally reveals the absence of a uniform commercial law structure in the SADC and the lack of supranational structures to adopt full panoply of business laws and to preserve the uniformity of laws in the member states. The findings from this thesis provide evidence that there is the need forthe development of a commercial law structure in the SADC and improvement of the current SADC structure. There is no doubt that thi swould do away with legal uncertainty in cross-border commercial transactions among SADC states.
Accepted: 2016-05-20T09:04:41Z URI: https://repository.up.ac.za/handle/2263/52731